A review of the entrepreneurial mindset / Mohammad Noorizzuddin Nooh - Nooh, Mohammad Noorizzuddin (UiTM Cawangan Kedah, 2022)
Entrepreneurship is a branch of study aimed at assisting students, individuals, and organisations with their entrepreneurial issues. It is necessary for the country's and society's economic development. Individuals, communities, and nations benefit from a wide range of social and economic benefits that entrepreneurship provides. The purpose of this article is to compile the results of early research on the content and method of establishing an entrepreneurial mindset. As a result, the current state of the literature on the concept of entrepreneurship has been consolidated, allowing researchers to better comprehend its origins, roots, and evolution. The author wishes to encourage youngsters to become entrepreneurs as early as primary school. They gain entrepreneurial experience, skills, and abilities as well as the ability to solve entrepreneurial difficulties as a result of their efforts. This article explains the concept of an entrepreneurial mindset in depth, making it easier for individuals and organisations to participate in interactive entrepreneurial activities in their daily lives. The purpose of this study is to conduct a literature review in order to have a better grasp of the concept of the entrepreneurial mindset. An in-depth explanation of the author's different primary subtopics will provide a comprehensive knowledge of the entrepreneurial mindset. The literature will explain the methods utilised to instil an entrepreneurial mindset in children, adolescents, adults, retirees, and people with disabilities. Furthermore, the literature will also rationalize the role of entrepreneurial education on the development of an entrepreneurial attitude.